(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the didactic potential of the Desmos platform in developing spatial reasoning among academic lyceum students. It explores the role of interactive graphical tools in shaping spatial thinking, enhancing cognitive engagement, and strengthening visual perception. The study is based on an experimental methodology, with statistical analysis of the results obtained from lessons conducted using the Desmos platform.